The Mysticism of Dream Interpretation from Tetamba Cirebon Manuscripts - Hidayani, Fika; Arfan, Am'mar Abdullah (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2022)
Information on dream interpretation is always interesting to study, especially when it is connected with mystical things. Due to limited abilities, not anyone can interpret dreams. Only people who are given a ‘gift’ can read about it. This research tries to interpret dreams that the sources from manuscripts entitled the Book of Tetamba. This book was written in Pegon script and Arabic and used Javanese Cirebon and Arabic. This research used qualitative research with an analytical descriptive approach, collecting data and materials from various sources. Then the content analysis used the content analysis method from Miles and Huberman’s theory which consists of data reduction, data display, dan conclusion drawing. By using the help of theories regarding mysticism, dream interpretation, and the connection between mysticism and dream interpretation, 10 classifications of dreams are produced, namely meeting the Prophet Muhammad, dreams of meeting the Prophet's companions, dreams of flying, dreams of seeing celestial bodies, and so on.